The Nursing Role in the Management of Medication Overuse Headache: Realities and Prospects - Luigi Alberto Pini; Katiuscia Cottafavi; Paola Ferri (Brain Sciences, 2024)
This review aims to analyze the current literature to identify articles related to the role of nurses and, in general, the nursing management of patients suffering from medication overuse headache (MOH), a globally spread disease. We specifically argue for non-pharmacological approaches to pain management, such as multidisciplinary team approaches, holistic treatment, cognitive behavioral therapy and exercise. For this review, we investigated international scientific databases, including PubMed, CINAHL, Scopus and Embase, in the period between 2000 and 2024. We observed a wealth of scientific articles related to MOH, but a poverty of articles relating to the nursing management of headache. The research included the presence of academic-level training for nurses, whereas there are few institutions that train competent professionals in both pharmacological and non-pharmacological management of MOH patients. Nursing assessment and assistance strategies are indicated to plan tailored treatment paths related to the specific needs of these patients.